2014
DOI: 10.1590/0004-282x20140082
|View full text |Cite
|
Sign up to set email alerts
|

Pull test performance and correlation with falls risk in Parkinson?s disease

Abstract: Postural instability (PI) and falls are major sources of disability in Parkinson's disease (PD). Our objectives were to evaluate the correlation between the pull-test (PT) scores and falls. Patients underwent a standardized data collection including demographic, clinical data, and the UPDRS scores for falls and the PT. Cases with scores .1 for falls were considered frequent fallers. 264 patients were included with mean age 67.6±10 years, mean age of onset 59.1±10.7 years. Comparison between PT scores versus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The quantitative tests used routinely are kinematic gait analysis, global mobility task, phase coordination index, ambulatory gait assessment, ambulatory freezing assessment, and the GAITRite system [47]. The pull test (PT), is reported to have the highest specificity and sensitivity when rightly performed and interpreted [48]. However, many studies have concluded that multiple balance tests assessing the different types of postural stress provide an optimal assessment of PI [48,49].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative tests used routinely are kinematic gait analysis, global mobility task, phase coordination index, ambulatory gait assessment, ambulatory freezing assessment, and the GAITRite system [47]. The pull test (PT), is reported to have the highest specificity and sensitivity when rightly performed and interpreted [48]. However, many studies have concluded that multiple balance tests assessing the different types of postural stress provide an optimal assessment of PI [48,49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The pull test (PT), is reported to have the highest specificity and sensitivity when rightly performed and interpreted [48]. However, many studies have concluded that multiple balance tests assessing the different types of postural stress provide an optimal assessment of PI [48,49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Matinollia et al analyzed mobility and balance in PD and noted that advanced age and severity of disease are related to mobility and impaired balance in patients with PD (23) . Munhoz and Tieve rated balance by retropulsion using the UPDRS test and found that age and severity of PD increase the level of difficulty for completion of the task (24) . We also analyzed the relationship between freezing of gait and mobility / performance of DT, and we observed that the low performance of DT and functional activities could be due to gait freezing.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because poor reactive postural control is associated with increased fall risk. 50 Furthermore, the FAB Scale and Mini-BESTest measure postural stability while performing a secondary task. It has been shown that patients with PD worsen in balance performance when focusing on a secondary task.…”
Section: Discussionmentioning
confidence: 99%